Editoras universitárias paranaenses : distribuição e circulação do livro universitário das instituições de ensino superior do Paraná - Martins, João Manoel (2016)
This work was dedicated to analysis and research of the University Book distribution problems, particularly publishers of the Public Universities of Paraná. We began our research by presenting a brief history of the book of the ways in Brazil, the university publishing activity, the number of Brazilian publishing market, the situation of the university issue in the country and public policies for the book, since the arrival of the royal family to the country. In the second chapter we investigate the Brazilian university field and subfield editorial, its relations with society, the pressures it suffers always supported the theory of social field of Pierre Bourdieu. The third chapter we use to analyze excerpts from interviews conducted with officers and servants of Paraná university presses, in order to collect data that subsidize our research, which could allow to point out the main problems affecting the university presses of Paraná state, so that the end this work could list them, and where possible to propose a way to solve, or at least a way to minimize them. We have carried out a history and literature, the history of the book and the Brazilian publishing market since the period of the empire to the present day, also investigated the trajectory of the leading publishers of Paraná state universities, the challenges of participation in the competitive publishing market.